Rationale for the IMAGINE study for chronic active antibody‐mediated rejection (caAMR) in kidney transplantation. (1st December 2022) - Nickerson, Peter W.
Abstract : Chronic active antibody‐mediated rejection (caAMR) in kidney transplantation is a major cause of late graft loss and despite all efforts to date, there is no proven effective therapy. Indeed, the Transplant Society (TTS) consensus opinion called for a conservative approach optimizing baseline immunosuppression and supportive care focused on blood pressure, blood glucose, and lipid control. This review provides the rationale and early evidence in kidney transplant recipients with caAMR that supported the design of the IMAGINE study whose goal is to evaluate the potential impact of targeting the IL6/IL6R pathway.